Impact of RSV infection on mortality, rehospitalization, and long-term pulmonary, cardiovascular, and functional outcomes in hospitalized adults: a systematic review and meta-analysis - Josef Yayan (Virology Journal)
Abstract Background Respiratory syncytial virus (RSV) is increasingly recognized as a significant pathogen in adults, particularly those with underlying comorbidities. However, the burden of RSV on post-hospital outcomes remains underexplored. This study aimed to assess the impact of RSV infection on mortality, rehospitalization, and long-term pulmonary, cardiovascular, and functional outcomes in hospitalized adults. Methods A systematic review and meta-analysis were conducted according to PRISMA 2020 guidelines. A comprehensive search of major databases until February 2025 identified cohort and observational studies reporting on clinical outcomes in adults with laboratory-confirmed RSV infection. A total of seven eligible studies encompassing 180,125 patients were included. Pooled odds ratios (OR) with 95% confidence intervals (CI) were calculated using a random-effects model. The risk of bias was assessed using the Newcastle–Ottawa Scale and the ROBINS-I tool. Funnel plots and Egger’s test were used to assess publication bias. Results RSV infection was associated with significantly increased 30-day mortality (OR 0.22, 95% CI: 0.12–0.41; P < 0.01, I² = 96%) and 90-day mortality (OR 0.30, 95% CI: 0.19–0.46; P < 0.01, I² = 97%). Although the odds ratios are below 1, this indicates higher mortality in RSV-positive patients, as the reference groups had lower risk. Statistically significant associations were also found for cardiovascular complications (OR 0.46, 95% CI: 0.33–0.64) and functional impairments (OR 0.57, 95% CI: 0.42–0.78). No significant association was identified for 90-day rehospitalization (OR 0.67, 95% CI: 0.39–1.14) or pulmonary impairments (OR 1.09, 95% CI: 0.79–1.50). Heterogeneity was high across most outcomes. Publication bias was only evident for the 30-day mortality outcome. Conclusions RSV infection in hospitalized adults is associated with elevated short- and medium-term mortality, as well as increased risk of cardiovascular and functional complications post-discharge. These findings highlight the need for RSV-specific prevention strategies, including vaccination and post-acute care planning, particularly for vulnerable adult populations. Clinical trial number Not applicable.